Hitlerinių okupantų piktadarybės naikinant Tarybų Lietuvos bibliotekas bei knygų fondus - Sinkevičius, Klemensas (Knygotyra, 1987)
Carrying out the subjugation policy in occupied countries hitler fascists decisively destroyed libraries and their book stocks. In Lithuania even in the first days of occupation they closed and destroyed all the libraries of the Communist party of Lithuania, Comsomol, Lithuanian people help union, trade union and other organizations, culture houses and cottage-reading rooms, part of state, public, school and scientific libraries. Nearly 2,5 thousand libraries have been fully destroyed. Communist, antifascist, pacifist literature, books written by Jewish authors and those of countries that were at war with Hitler Germany had to be taken out of stocks from all the left libraries. More valuable publications were transported to Germany. In Lithuania in the years of occupation hitlerites destroyed and carried out from the country more than 3 million books. Only state public, libraries lost 0,5 million books, that is 2/3 of pre-war book stocks.